Characterization of human papillomavirus genotypes in women attending the Comprehensive Care Unit for HIV and Chronic Infections of a Guatemalan hospital - Pereira, Rocío; Navas-Castillo, Jessenia; Samayoa-Bran, Ana (Revista Acciones Médicas, 2023)
HIV infection suppresses the immune system by increasing the risk of acquiring high-risk human papillomavirus (HR-HPV) infection, persistence, and ultimately development of cervical cancer. Objective: To characterize the HPV genotypes, describe the sociodemographic and epidemiological characteristics, and establish the association between HPV and clinical monitoring variables in HIV-positive women who attended the UAI-HR from March 2019 to August 2021. Method: Retrospective descriptive-cross-sectional study in 406 women with HIV. A non-probabilistic sampling of consecutive cases was carried out; the data were analyzed in the Jamovi software, by calculating frequencies and percentages for categorical variables and through contingency tables, using the chi-square test. Results: A frequency of HR-HPV genotypes of 36.95% (150/406) was found, with a predominance of other HR-HPVs (95, 76.0%). The age range that occurred the most (58, 39.5%) was 30 to 39 years. The highest frequency of positivity for HR-HPV genotypes was in patients with counts greater than 500 cells/µL (30.6%, 66) and with undetectable HIV viral loads (28.3%, 53). Conclusion: The frequency of HR-HPV genotypes shows the importance of screening for it in patients recently diagnosed with HIV, as well as the periodic search for HPV in all women who are negative in their first test.